PEMAKSIMALAN FUNGSI MESJID SEBAGAI BASIS EKONOMI JAMAAH DI MESJID RAYA SALIMPAUNG - M.Ag, Dr. Rizal (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2010)
This research was aimed at raising awareness among Moslem communities (jama’ah) toward the efforts of maximizing the roles of the mosques in improving the welfare of the societies by means of empowering economic institution of the mosques. To realize the aims, participatory action research (PAR) approach was employed. To collect the date, participative steps were applied. The findings showed that significant involvement of the board of the mosques, boards of financial institution (koperasi) of thed mosques and officers of local government (nagari) in every meetings, discussions and plannings for further meetings. They were also motivated to establish economic institutions for their mosques, such as: BMT and KJKS. Based on the findings, it is recommended that continuity of the program under the supports from STAIN Batusangkar and Local Government of Tanah Datar should be of concern.